Hubungan Kelengkapan Fasilitas Bengkel terhadap Hasil Belajar Teknik Pemesinan Bubut Siswa Kelas XI SMK Negeri 1 Bukittinggi - Wandi, Faiz; Erizon, Nelvi (MASALIQ, 2024)
Facilities in workshops have a significant impact on the achievement of learning outcomes. This study aims to explore the relationship between the completeness of workshop facilities and the achievement of learning lathe machining techniques for grade XI students at SMK Negeri 1 Bukittinggi. The research approach used was quantitative correlational with a population of 64 students, and 32 students were taken as samples using the simple random sampling method. The measuring device used is a questionnaire with 34 items. The results showed that the completeness of workshop facilities was rated high with a percentage of 75%, while student learning outcomes were less than 75% with a percentage of 40.6%. Through the correlation hypothesis test, it was found that R count (0.450) < R table (0.349), indicating that there was significant relationship between the completeness of workshop facilities and the learning outcomes of lathe machining techniques for grade XI students at SMK Negeri 1 Bukittinggi.